Robust hybrid control law for a boost inverter. (August 2020) - Albea-Sanchez, Carolina; Garcia, Germain
Abstract: A robust hybrid control for a boost inverter is proposed in this paper. This control presents the particularity of considering the real nature of the dynamics, which means, the continuous-time dynamics, voltages and currents, and the discrete-time dynamics, the switching of the transistors. Likewise, due to implementation issues a minimum dwell time is introduced in the control loop scheme. Uniform global asymptotic stability is guaranteed, ensuring that the tracking error of the system output enters into a small neighborhood of zero. Moreover, robustness guarantee with respect to parameter variations, in terms of an error tracking output regulation, are also provided here. The effectiveness of the proposed hybrid control scheme is illustrated in simulation.